Analysis of The Implementation of The Assistance Service Policy at The Partnership Empowerment Center at The Center For Financial Transaction Reporting and Analysis (PPATK) - Harsanti, Diah Retno; Cholifihani, Muhamad; Rustanto, Agung Edi (Yayasan Riset dan Pengembangan Intelektual, 2025)
The study aims to analyze the implementation of assistance service policies at the Partnership Empowerment Center (Pusdamitra) of PPATK using Edward III’s framework, which includes communication, resources, disposition and bureaucratic structure. A qualitative approach involving interviews, document analysis, and observations was employed to explore the supporting and hindering factors in implementation. The finding reveal solid internal communication but highlight gaps in information delivery to external stakeholders. Key challenges include limitations in expertise and cross-unit coordination, while complex bureaucracy reduces efficiency. Recommendations include improving accessibility and communication formats, providing formal training and strengthening human resources, optimizing technology and digital services, developing formal SOPs and strengthening evaluation, and improving coordination and supervision.